Fast preparation of controllable nitrogen-atom-substituted graphyne film for use in field effect transistor devices. (13th October 2021) - Yang, Ze; Ren, Xin; Ma, Xiaodi; Song, Yuwei; Hu, Xiuli; Zhang, Mingjia; Li, Yuan; Xie, Chipeng; Li, Xiaodong; Li, Jiazhu; Huang, Changshui
Abstract : A modified interface synthesis was developed for fast preparation of graphyne derivates that are comprised of aza-aromatics and acetylenic linkers, providing some reference for understanding the properties of graphyne-based versatile materials. Abstract : It has been predicted that the introduction of heteroatoms into graphyne (GY) will be able to improve the properties of GY and increase its range of applications. However, it is difficult to synthesize GY, which is linked through only one acetylenic bond (–CC–) between any two adjacent benzene rings. Herein, we demonstrate an innovative interfacial synthetic method for rapid preparation of nitrogen-substituted GY (N-GY) films. Notably, as-prepared N-GY films that offer a determined morphology and well-established N atoms can be utilized as semiconductor films for field-effect transistor (FET) devices. With the increase in the number of N atoms in N-GY films, the carrier mobility of the prepared FET devices based on those N-GY films was increased. An average mobility of 9.8 cm 2 V −1 s −1 with a gate operating voltage lower than 5 V was measured for such rapidly prepared N-GY films, implying that interfacial synthesis can provide a facile avenue to obtain GY-based electronic materials. Thus, GY-based materials have the potential to become very promising candidates for incorporation into electronic devices.